Wizards and scientists explorations in Afro-Cuban modernity and tradition - Palmié, Stephan 1959- (Duke Univ. Press, 2002)
In "Wizards and Scientists" Stephan Palmie offers a corrective to existing historiography on the Caribbean, focusing on developments in Afro-Cuban religious culture to demonstrate that traditional Caribbean cultural practices are steeped in the same history that produced modernity and represent complex hybrid formations. Palmie argues that the standard narrative trajectory from tradition to modernity, and from passion to reason, is a violation of the synergistic processes through which cultures develop historically specific, moral communities. Highlighting the ways that Afro-Cuban discourses serve as means of moral analysis of social action, Palmie suggests that the irrational premises of religious structures not only rival Western rationality in analytical acumen but are integrally linked to rationality itself.Afro-Cuban religion is as 'modern' as nuclear thermodynamics, he claims, just as the Caribbean might be regarded as one of the first truly 'modern' locales: its plantation export economy and appropriation and destruction of human bodies for profit anticipated the industrial revolution in the metropolis by more than a century.Working to prove that modernity is not just an aspect of the West, he focuses on those whose physical abuse and intellectual denigration was the price paid for modernity's achievement. All cultures influenced by the transcontinental Atlantic economy share the legacy of slave commerce, and local forms of moral imagination have developed distinctive yet extremely interrelated responses to this violent past and contradiction-ridden postcolonial present.
Keywords: Godsdienst; Moderniteit; Negers; Religieuze gebruiken; Religion; Schwarze; Blacks -- Cuba -- Religion; Afroamerikanischer Synkretismus; Kubaner; Cuba -- Civilization -- Western influences; Cuba -- Religion; USA; Kuba